4(3x-8)-3=4(x-2)+21

Simple and best practice solution for 4(3x-8)-3=4(x-2)+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-8)-3=4(x-2)+21 equation:


Simplifying
4(3x + -8) + -3 = 4(x + -2) + 21

Reorder the terms:
4(-8 + 3x) + -3 = 4(x + -2) + 21
(-8 * 4 + 3x * 4) + -3 = 4(x + -2) + 21
(-32 + 12x) + -3 = 4(x + -2) + 21

Reorder the terms:
-32 + -3 + 12x = 4(x + -2) + 21

Combine like terms: -32 + -3 = -35
-35 + 12x = 4(x + -2) + 21

Reorder the terms:
-35 + 12x = 4(-2 + x) + 21
-35 + 12x = (-2 * 4 + x * 4) + 21
-35 + 12x = (-8 + 4x) + 21

Reorder the terms:
-35 + 12x = -8 + 21 + 4x

Combine like terms: -8 + 21 = 13
-35 + 12x = 13 + 4x

Solving
-35 + 12x = 13 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-35 + 12x + -4x = 13 + 4x + -4x

Combine like terms: 12x + -4x = 8x
-35 + 8x = 13 + 4x + -4x

Combine like terms: 4x + -4x = 0
-35 + 8x = 13 + 0
-35 + 8x = 13

Add '35' to each side of the equation.
-35 + 35 + 8x = 13 + 35

Combine like terms: -35 + 35 = 0
0 + 8x = 13 + 35
8x = 13 + 35

Combine like terms: 13 + 35 = 48
8x = 48

Divide each side by '8'.
x = 6

Simplifying
x = 6

See similar equations:

| 3=30+30 | | 49x^2+5x=1500 | | 24x+66=-66+27x | | f(2)=7-5 | | 4(3x-2)+27=6x+1 | | 27+x+44=180 | | 400=0.05(x-520) | | 5x-9y=-15 | | -23=4x-6x | | 1.1p+14=16 | | 5(3x-9)-6=5(x-3)+24 | | 2x^2+2x=264 | | -1-2w=-4 | | -3-(-5-2n)-6(1-5n)=9 | | 9+8m=6m-3 | | 2x-9+6x=-3(3+5x) | | [1+3c]-18=-8 | | 9+8m=-3 | | 4-3w=8.5 | | 3y-6x=-33 | | F[x]=2x+12 | | -10w=15 | | x(x+4)=6(2) | | 9=v+6-2 | | (5x)=-18 | | (2x+20)=(3x-10) | | 3(2x+1)-5x=2(x+1)-3 | | (2x-20)=(3x-10) | | 15=12x^2+24x | | 4d+8-2d=6d-10 | | -12x+2y=x+2 | | 7xy-4xy+2xy+6xy+3xy-7xy= |

Equations solver categories